Deconstruction of Dictatorship in Jorge Mario Pedro Vargas Llosa’s Works - Nasrin Haghighat Chaleshtari; Ali Omidi (Journal of Language and Literature, 2021)
Latin America's literature does not merely represent the creation of literary masterpieces for artistic enjoyment; instead, it is inspired by real-world events. Latin American authors attempt to depict the pains, sufferings, and problems they have always grappled with. Taking a descriptive-analytic approach by applying sociological criticism, the present study attempted to examine Jorge Mario Pedro Vargas Llosa’s most essential works on dictatorship rule, including Conversación en La Catedral, La guerra del fin del mundo, La ciudad y los perrosand La fiesta del chivo. One of the Latin America’s political typical features was fascism and dictatorship, which was reflected in different authors' works, including Llosa. The findings of the present study revealed that the dictatorial system raised in Llosa’s works is characterized by violence, political and economic corruption, intervention by foreign powers, the emergence of Communism as the sole savior of the third world, and the elites’ disenchantment with improvement in the status of the society. He put forward this sober idea that dictators are not natural catastrophes, but they are constructed as dictators by their victims.